If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + -1q = p Reorder the terms: -1q + s = p Solving -1q + s = p Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1s' to each side of the equation. -1q + s + -1s = p + -1s Combine like terms: s + -1s = 0 -1q + 0 = p + -1s -1q = p + -1s Divide each side by '-1'. q = -1p + s Simplifying q = -1p + s
| -2n=-3n+6 | | -16+x=7 | | 216/18 | | -14n+12=-10n-16 | | 4(c-8)=3(5+c) | | x/5=0 | | -15=6+X | | 0.5(2x-8)=7x+10 | | 18=2x+4x | | 1/2g=31/3 | | x-100/5.3 | | -5=x-(-1) | | t/5-3=7 | | 8x+3=6x+13 | | 81k-5=400 | | 2/9+2 | | 3a-5a+1=11 | | 4-5k=8+k | | 1/2x+x-9=180 | | -7=3t-15-t | | 87=3w | | 2x+6=19x | | 2x+(0)=5 | | p-7=-3+9p | | 3-x=2x-27 | | 10w-8=9+7w | | 2x+6x=18 | | 43y=301 | | 19x+27=103 | | 7x^2=16+x | | 4-3x=31 | | x-3=24 |